تداولية الأفعال الكلامية في كتاب كليلة ودمنة لابن المقفع " نماذج مختارة " - لكحل، نسرين, طلحة، هاجر (جامعة الوادي University Eloued, 2019)
ملخص الدراسة: الملخص: تناولنا في دراستنا الموسومة بــــ "تداولية الأفعال الكلامية في كتاب كليلة ودمنة -دراسة تداولية- والتي كان أساسها المنهج التداولي, الذي أبرز لنا أهم المقاصد المباشرة وغير مباشرة، التي جاءت على شكل حوار الذي يظهر اللغة بمستوييها التفاعلي والتواصلي، من خلال ما يدور بين "دبشليم " الملك و"بيدبا" الفيلسوف قصد التأثير والتأثر والاقناع. لقد كان هناك تنوع للأفعال الكلامية عند العرب وعند الغرب، رغم عدم تواجد مصطلح التداولية أنذاك عند العرب، لكن كانت هناك بعض التلميحات التي تجلت في الخبر ولإنشاء لغرض دراسة اللغة وربطها بمقاصد مستعمليها، وهذا ما توصل اليه الغرب في دراسات أوستين (Austin) وسيرل (Searle)، التي كان لها نفس الغاية والهدف، كما أن السياق وحدة أساسية ساهمت في إنجاح العملية التواصلية وبلوغ المقاصد وبالتالي الوصول إلى هدف الاقناع . كما اعتمدت دراستنا على مدخل تمهيدي, وفصلين :الأول :الفعل الكلامي من المنظور الغربي في كليلة ودمنة ,أما الثاني معنون ب:الفعل الكلامي من المنظور العربي في كليلة ودمنة كما أثبتت الدراسة في الأخير أن هذا الكتاب كان شاهد على عصر" ابن المقفع" ولا يزال من أهم الكتب التي لها غايات إرشادية تعليمية، يستفيد منها العام والخاص وكانت أغلب مقاصده خلف استراتيجية تلميحيه تبرز طبقات اللغة ومستعمليها ومتداوليها، وهذا جعل الكتاب يحظى بالعالمية وذلك ما احتواه من قيم سياسية واجتماعية وأخلاقية وتعليمية وتربوية . Abstract In our study, we have dealt with the "deliberative verbs in the book Kalila and Dimna - a deliberative study - which was the basis of the deliberative method, which highlighted the most direct and indirect purposes, which came in the form of dialogue, which shows the language in terms of interactive and communicative, King "and" Bedba "philosopher meant to influence and influence and persuasion. There was a variety of verbal acts among the Arabs and the West, although there was no Arabic term for deliberation at that time, but there were some hints that were revealed in the news and for the establishment of the purpose of studying the language and linking it to the purposes of its users. This is what the West found in the studies of Austin, Searle, which had the same purpose and purpose, and the context is a key unit contributed to the success of the communication process and achieve the goals and thus reach the goal of persuasion. Our study is based on a preliminary introduction, and two chapters: the first: the verbal act from the Western perspective in Kalila and Damnah, the second is entitled: The verbal act from the Arab perspective in Kalila and Damnah The study also proved in the latter that this book was a witness to the age of "Ibn al-Muqafa" and it is still one of the most important books that have instructive educational purposes, benefiting the public and private and most of its purposes were behind the strategy of pupils highlighting the layers of the language and its users and traders, Its content is of political, social, moral, educational and educational values. .
Keywords: التداولية _ الأفعال الكلامية _ القصدية _ كليلة ودمنة; pragmatique _ Verbal verbs _ The intentional _ Kalila and Dimna.